Designing Graphical User Interface (GUI) for Adjustable Robust Maximum Flow Problem - Diah Chaerani; Elis Hertini; Endang Rusyaman; Naufal Badruzzaman (Jurnal Matematika Integratif, 2021)
Maximum flow problem is one of optimization problems which aims to find the maximum flow value that is traversed in a network system. This problem can be solved using existing algorithms and linear programming. In the case of maximum flow, often the parameters used vary due to certain factors. \cite{agustini} designed the Robust Counterpart Optimization Model for Maximum Flow Problems by assuming side and flow capacities from an indefinite point to destination point to solve the maximum flow problem with uncertainty. To facilitate the search for solutions with large amounts of data, a Graphical User Interface (GUI) was made. GUI is a pictorial interface of a program that can facilitate its users in completing their work such as counting, making, and so on. In this study, the GUI was created using Maple software and used the Adjustable Robust Counterpart Optimization Model made by \cite{agustini}. Thus, the search for solutions to maximum flow problems can be resolved quickly and efficiently only by entering the data needed for calculations in the GUI.